2014
DOI: 10.1021/ol500136x
|View full text |Cite
|
Sign up to set email alerts
|

AlCl3-Promoted Formal [2 + 3]-Cycloaddition of 1,1-Cyclopropane Diesters with N-Benzylic Sulfonamides To Construct Highly Stereoselective Indane Derivatives

Abstract: An unprecedented AlCl3-promoted formal [2 + 3]-cycloaddition of 1,1-cyclopropanes with readily available N-benzylic sulfonamides has been developed. Experimental evidence supports an unusual mechanism wherein the donor-acceptor cyclopropane serves as a source of 2-styrylmalonate rather than the "classical" 1,3-dipole. A broad range of 1,1-cyclopropanediesters undergo a carbocation-initiated cyclization reaction with N-benzylic sulfonamides to afford highly functionalized Indane derivatives in a fast and high-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…On the basis of above result and literature precedent (Scheme ), we assumed that MgI 2 activates the DACs 1 and converts it into the opened ring 1,3‐zwitterion intermediate A . It further isomerises to 2‐styrylmalonate complex B .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…On the basis of above result and literature precedent (Scheme ), we assumed that MgI 2 activates the DACs 1 and converts it into the opened ring 1,3‐zwitterion intermediate A . It further isomerises to 2‐styrylmalonate complex B .…”
Section: Resultsmentioning
confidence: 87%
“…In 2014, Wang et al . reported AlCl 3 ‐promoted formal [2+3]‐cycloaddition of DACs with N ‐benzylic sulphonamides where DACs serves as a source of 2‐styrylmalonate . Recently, Tomilov and his co‐worker reported cycloaddition of 2‐styrylmalonate, an alternative of DAC, with aldehydes, to afford dihydropyranones .…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated cyclopropane compounds are excellent and useful building blocks in organic synthesis. Recently our group was interested in D−A cyclopropanes as useful synthons (Scheme a), as well as rare earth Lewis acid as valuable catalyst . For example, in 2017, we developed Sc(OTf) 3 catalyzed reaction of D−A cyclopropane with tertiary alcohol (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, D–A cyclopropanes can also act as sources of 1,2‐ and 1,4‐dipoles under Lewis acid conditions. Recently, our group revealed that D–A cyclopropanes could undergo reactions as less‐developed 1,2‐dipoles in formal [2+3]‐cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%